Synthesis, carbonic anhydrase I and II inhibition studies of the 1,3,5-trisubstituted-pyrazolines - Halise Inci Gul; Ebru Mete; Parham Taslimi; Ilhami Gulcin; Claudiu T. Supuran (Taylor & Francis Group, 2017)
4-(3-(4-Substituted-phenyl)-5-phenyl-4,5-dihydro-1H-pyrazol-1-yl) benzenesulfonamides (9-16) were successfully synthesized and their chemical structures were confirmed by 1H NMR, 13C NMR, and HRMS spectra. Carbonic anhydrase I and II inhibitory effects of the compounds were investigated. Ki values of the compounds were in the range of 316.7 ± 9.6-533.1 ± 187.8 nM towards hCA I and 412.5 ± 115.4-624.6 ± 168.2 nM towards hCA II isoenzymes. While Ki values of the reference compound Acetazolamide were 278.8 ± 44.3 nM and 293.4 ± 46.4 nM towards hCA I and hCA II izoenzymes, respectively. Compound 14 with bromine and compound 13 with fluorine substituents can be considered as the leader compounds of the series because of the lowest Ki values in series to make further detailed carbonic anhydrase inhibiton studies.